Cláusulas de indemnización en operaciones privadas de M&A en México - Garibay Güémez, Francisco Javier (2023)
The indemnity clause is recurrently implemented in sale and purchase agreements, in order to distribute the risk assumed by the parties with respect to the different unforeseen risks and possible defaults. In the case of M&A transactions, a correct allocation of risks during negotiations is indispensable; for which a full knowledge of the characteristics and elements of the indemnity clause is required.Therefore, this article will address the following topics. On the one hand, the primary content and parties subject to the indemnity clause. In addition to addressing the different elements and concepts that compose and affect it. On the other hand, explore the limits and exceptions to its implementation.